First Nations Version : an indigenous translation of the New Testament. (InterVarsity Press, 2021)
"The First Nations Version (FNV) is a retelling of the Creator's Story-the Scriptures-following the tradition of the storytellers of these oral cultures. While remaining faithful to the original language of the New Testament, the FNV is a dynamic equivalence translation that captures the simplicity, clarity, and beauty of Native storytellers in English." --